Exploring the limitations of the Hantzsch method used for quantification of hydroxyl radicals in systems of relevance for interfacial radiation chemistry. (January 2017) - Yang, Miao; Soroka, Inna; Jonsson, Mats
Abstract: In the presence of Tris or methanol, hydroxyl radicals in systems of relevance for interfacial radiation chemistry can be quantified indirectly via the Hantzsch method by determining the amount of the scavenging product formaldehyde formed. In this work, the influence of the presence of H2 O2 on the Hantzsch method using acetoacetanilide (AAA) as derivatization reagent is studied. The experiments show that the measured CH2 O concentration deviates from the actual concentration in the presence of H2 O2 and the deviation increases with increasing [H2 O2 ]0 /[CH2 O]0 . The deviation is negative, i.e., the measured formaldehyde concentration is lower than the actual concentration. This leads to an underestimation of the hydroxyl radical production in systems containing significant amount of H2 O2 . The main reason for the deviation is found to be three coupled equilibria involving H2 O2, CH2 O and the derivative produced in the Hantzsch method. Highlights: Hydroxyl radicals can be indirectly quantified by quantifying CH2 O. The Hantzsch method using acetoacetanilide is used to determine CH2 O. H2 O2 negatively interferes with the detection of CH2 O. Interference depends on [H2 O2 ]0 /[CH2 O]0 . Interference is caused by the coupled equilibria.